Describing behaviour: a philosophical analysis - Bunting, I A (Rhodes University, Faculty of Humanities, Department of Philosophy, 1966)
Questions revolving around the possibility and justifiability of reductive analyses of the concept 'not', lie at the heart of many of the problems in the philosophical interpretation of not-descriptions. In this thesis, I wish to show, by discussing various problems in the logic of not-descriptions, that, and why, reductive analyses must be unsatisfactory.
Keywords: Human behaviour -- Philosophy; Analysis (Philosophy)